Sensitivity Analysis and Financial Decisions - Gaytán Cortés, Juan (Mercados y Negocios, 2022)
The sensitivity analysis illustrates the variation of the value or result of a model in response to changes in some of its key variables, keeping the value of the other variables constant. The sensitivity analysis is carried out considering one variable at a time and always assuming that there is independence between the different variables that influence or determine the value in the model.